Error Modeling in Distance and Rotation for Self-Calibration of Space Robots on Orbit - Qingxuan Jia; Shiwei Wang; Gang Chen; Hanxu Sun (International Journal of Aerospace Engineering)
Vibration and impact of launching, inner and outer pressure difference, and thermal deformation of the space capsule will change the transformation between the pose measurement system and the space robot base. It will be complicated, even hard, to measure and calculate this transformation accurately. Therefore, an error modeling method considering both the distance error and the rotation error of the end-effector is proposed for self-calibration of the space robot on orbit, in order to avoid the drawback of frame transformation. Moreover, according to linear correlation of the columns of the identification matrix, unrecognizable parameters in the distance and rotation error model are removed to eliminate singularity in robot kinematic calibration. Finally simulation tests on a 7-DOF space robot are conducted to verify the effectiveness of the proposed method.